The Effect of Profitability, Liquidity, Leverage and Company Size on the Company's Dividend Policy - Menik Indrati; Kristine Amelia (Budapest International Research and Critics University, 2022)
This study aims to test and analyses the effect of Profitability, Liquidity, Leverage and Company Size on Dividend Policy in the LQ45 index company sector listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. This study used the causality method. The population in this study was 45 companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period with a purposive sampling technique. The data analysis technique used is multiple regression analysis using SPSS version 26. The hypothesis test consists of a simultaneous test (statistical test F), a partial test (statistical test T), and a multiple linear regression test. The results of this study show that simultaneously the variables of Profitability, Liquidity, Leverage and Company Size affect the company's Dividend Policy. Partially, the Profitability variable affects dividend policy, and leverage negatively affects dividend policy. Meanwhile, the liquidity and company size variables do not affect the Dividend Policy.